Clinic-Based Retrospective Analysis of Psychopharmacology for Behavior in Fragile X Syndrome - Elizabeth Berry-Kravis; Allison Sumis; Crystal Hervey; Shaguna Mathur (International Journal of Pediatrics)
Fragile X syndrome (FXS) is associated with behavior that limits functioning, including distractibility, hyperactivity, impulsivity, hyperarousal, anxiety, mood dysregulation, and aggression. Medication response and side effect data were reviewed retrospectively for 257 patients (age 14±11 years, range 4–60 years, 203 M, 54 F) attending an FXS clinic. Treatment success rates were defined as the percentage of positive response in the form of documented clinical report of improvement in the behavior(s) being targeted over at least a 6-month period on the medication, without side effects requiring medication discontinuance, while failures were defined as discontinuance of medication due to lack of clinical effectiveness or side effects. Success rate for treatment of targeted behaviors with trials of individual medications was 55% for stimulants, 53% for antidepressants, 62% for alpha2-agonists, and 54% for antipsychotics. With sequential trials of different medications in the same class, success rate improved to 73–77%. Side effect-related failures were highest for antipsychotics. Systematic psychopharmacologic intervention targeted to behavioral symptoms appears helpful in the majority of patients with FXS.